Pengetahuan Perpajakan, Sanksi Pajak Kesadaran Wajib Pajak dan Kepatuhan WPOP Sektor UMKM - Kartikasari, Ni Luh Gede Santhi; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 31 No 4 (2021), 2021)
The purpose of this study was to examine the effect of tax knowledge, tax sanctions, and awareness of taxpayers on MSME sector taxpayer compliance. A total of 98 individual taxpayers of the MSME sector were selected as respondents using the Slovin formula. The sampling method in this study is accidental sampling and the data analysis technique of this study uses multiple linear regression analysis. The results of this study indicate that tax knowledge, tax sanctions and awareness of taxpayers have a positive effect on tax compliance of SMEs. Keywords: Time Budget Pressure; Pressure Management; Locus of Control; Dysfunctional Behavior; Auditor Performance.